Adverse skin reactions following percutaneous bone conduction implant surgery using the linear incision technique with and without subcutaneous tissue reduction. (1st February 2017) - Van der Gucht, Karen; Vanderveken, Olivier; Hamans, Evert; Claes, Jozef; Van Rompaey, Vincent; Van de Heyning, Paul
Abstract: Conclusions: Adverse skin reactions were equally distributed among age groups, surgical technique, or presence of a retroauricular incision. Implant loss was observed more frequently in children when compared to adults and elderly. Objective: A bone conduction (osseointegrated) implant can be used for rehabilitation of patients with conductive hearing loss or single-sided deafness. The surgical technique has been modified to minimize adverse skin reactions and other complications. Two commonly used techniques are the linear incision technique with subcutaneous tissue reduction and the technique without tissue reduction. The primary aim is to compare the complication rate between the two surgical techniques. Methods: Retrospective study on all bone conduction implant cases implanted between April 1990 and July 2014 at a tertiary referral center. Skin reactions were graded by Holgers' scale (grade 0–1: 'normal', grade 2–3: 'adverse'). The worst follow-up available was reported. Results: Of the 289 bone conduction implants, 25 were implanted in children, 220 in adults, and 44 in elderly. Implant loss occurred in 2.8% of all cases: 8.0% in children, 2.3% in adults, and 2.3% in the elderly. Skin overgrowth was seen in 4.2%: 4% in children, 4.8% in adults, and 3.5% in the elderly. No differences were observed in the amount of adverse skin reactions (16.8% vs 14.7%) or skin overgrowth (4.6% vs 2.9%) between the surgical techniques. There was no difference in adverse skin reactions if the patient had a retroauricular incision (14.4% with vs 17.8% without prior incision).